(untitled) (Sains Humanika, 2023)
The purpose of this study is to learn about teachers’ perceptions of children’s readiness skills by understanding the different types of skills and their importance to children who will enter primary school in the future. There are 4 main objectives in this study which are (i) to explore the types of children’s readiness skills; (ii) to explore teachers’ perceptions of children’s readiness skills; (iii) to find out the relationship between teachers’ perceptions and children’s readiness skills; and (iv) to find out the difference between male and female teachers’ perceptions towards children’s readiness skills. This study is a quantitative study where it was only conducted using a survey method which is a set of questionnaires was distributed to 112 participants consisting of trainee teachers, young teachers, experienced teachers, and early childhood education practitioners in Selangor. The data were analyzed by using Statistical Software Package for Sciences (SPSS) version 25 to obtain percentage, standard deviation and mean. Findings show teachers understand the level of readiness skills required by children in kindergarten. Besides, their perceptions of the readiness skills needed by children is also at a good level. Several suggestions have been made to the Malaysian Ministry of Education to ensure that the emphasis on child well-being through positive learning is implemented in kindergarten so that children can improve their readiness skills when they are entering the primary school. Furthermore, researchers have stated the implications on children’s readiness skills, specifically the role of the school and parents in providing opportunities for them to explore their surrounding so that they demonstrate a clear nature of readiness to learn.